A Study on the Impact of Actuarial Assessment Tools on Probation Practices in Ontario - Silva-Roy, Maria-Cleusa (Université d'Ottawa / University of Ottawa, 2020)
There has been a rising concern surrounding risk within society. This increasing concern has dominated almost all aspects of human life and more specifically the way in which citizens are governed. How risk is addressed in general has shifted significantly; given this, the criminal justice system has also seen an escalation in concerns surrounding risk. Subsequently, there has been a push towards evaluating said risks through the use of actuarial assessment tools. Research has shown that with the rising reliance on actuarial assessment tools came the decrease in practitioner’s ability to rely on their professional judgement when conducting their work. However, there has been a gap identified in the literature. This gap pertains to how practitioners, particularly, probation officers perceive the impact of these actuarial tools on their work. This study aims to analyse how probation officers, within the province of Ontario, view the impact of actuarial assessment tools on their work. This study is guided by the theory of governmentality, as coined by Michel Foucault. In order to explore the impact of actuarial assessment tools on the practice of probation, seven semi-structured interviews were conducted with former probation officers. The perceptions varied and participants did not provide a unique and monolithic response; rather, the voices of all participants were shared to create a larger picture of how actuarial assessment tools impact the work of practitioners in the practice of probation.
Keywords: Risk assessment; Actuarial assessment tools; Risk society; Probation; Governmentality